2014
DOI: 10.1007/7854_2014_290
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Schizophrenia and Bipolar Disorder

Abstract: The role of stress in precipitating psychotic episodes in schizophrenia and bipolar disorder has long been acknowledged. However, the neurobiological mechanism/s of this association have remained elusive. Current neurodevelopmental models of psychosis implicate early dysfunction in biological systems regulating hypothalamic-pituitary-adrenal axis and immune function, with long-term effects on the development of the brain networks responsible for higher order cognitive processes and stress reactivity in later l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 147 publications
(147 reference statements)
1
12
0
Order By: Relevance
“…To verify the distribution of deficits in speed‐dependent functions, we performed a further cluster analysis only among patients with high educational attainment, which may be considered as an index of pre‐morbid intellectual level (DeQuardo, Goldman, Tandon, McGrath‐Giroux, & Kim, ; MacCabe et al ., ). Our results are in line with previous studies, which claim that there are different subtypes of schizophrenia, characterized by different intellectual paths after the onset (Černis et al ., ; Green et al ., ; Van Winkel et al ., ). These results could sustain the hypothesis that following psychosis onset, IQ is stable and that it is IQ at psychosis onset rather than pre‐morbid IQ predicts a more severe illness (Leeson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the distribution of deficits in speed‐dependent functions, we performed a further cluster analysis only among patients with high educational attainment, which may be considered as an index of pre‐morbid intellectual level (DeQuardo, Goldman, Tandon, McGrath‐Giroux, & Kim, ; MacCabe et al ., ). Our results are in line with previous studies, which claim that there are different subtypes of schizophrenia, characterized by different intellectual paths after the onset (Černis et al ., ; Green et al ., ; Van Winkel et al ., ). These results could sustain the hypothesis that following psychosis onset, IQ is stable and that it is IQ at psychosis onset rather than pre‐morbid IQ predicts a more severe illness (Leeson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such a unified model would explain the huge clinical heterogeneity which characterizes schizophrenia onset, course and outcome. According to other studies, a subgroup of subjects developing the disorder would exhibit neuropsychological impairment, more pronounced negative symptoms and a lower IQ (Černis et al ., ; Davidson & Weiser, ), while another subgroup of subjects, crucially exposed to social stressors (Green, Girshkin, Teroganova, & Quidé, ), would develop a subtype of the disorder characterized by more pronounced positive symptoms, maintaining a normal IQ not deteriorating after the onset (Van Winkel et al ., ). Therefore, it is possible to hypothesize that cognitive and intellectual heterogeneity in patients with schizophrenia might be related to the interplay between multiple factors including both neurodevelopmental and degenerative processes.…”
Section: Introductionmentioning
confidence: 99%
“…This model says that in especially vulnerable individuals (e.g., genetically vulnerable) stress represents an additional risk for the outbreak of the schizophrenic disease. An increased vulnerability of the offspring was shown—in addition to genetic vulnerability—if an inflammatory response was induced in the mother during the second trimester of pregnancy or in the offspring during later stages of CNS development in animal models (Giovanoli et al, 2013 ; Green et al, 2014 ). A recent study, the first large-scale epidemiological study in psychiatry, showed, however, that severe infections and autoimmune disorders increase additively the risk of schizophrenia and schizophrenia spectrum disorders also in adults (Benros et al, 2011 ).…”
Section: The Vulnerability-stress-inflammation Model Of Schizophreniamentioning
confidence: 99%
“…Psychological stress is a risk factor for both schizophrenia and PLEs (Campbell & Morrison, 2007;Green, Girshkin, Teroganova, & Quidé, 2014). It is defined as the extent to which an individual's life situations outweigh their ability to cope (Lazarus, 1966).…”
Section: Introductionmentioning
confidence: 99%